Crucial Conversations (getAbstract Summary). - , getAbstract (linkedin.com, 2020)
Learn how to have—and succeed at—high-stakes conversations in this audio-only summary of the popular book by Kerry Patterson, Joseph Grenny, Ron McMillan, and Al Switzler.